STAFF EXPENSES AND ITS EFFECT ON THE BANK’S NET PROFIT - Budhathoki, Prem Bahadur; Rai, Chandra Kumar (Researcher: A Research Journal of Culture and Society, 2018)
The aim of the study is to explore the relationship between a net profit of Nepalese commercial banks with staff expenses and staff bonus. This study is based on panel data which is collected from five sampled banks through the review of the annual report during the study period of fiscal year 2012/13 to 2016/17. These collected data are analyzed by using descriptive statistics, Pearson correlation coefficient, and log-log multiple regression models. The Mini-Tab software is used for the analysis of data. The results indicate that the predictor variable staff expenses do not significantly impact on net profits of the bank even though they are positively correlated. On the other hand, the response variable (net profit) is significantly affected by the predictor variable staff bonus. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 63-71